Competition Law, Regulation and SMEs in the Asia-Pacific : Understanding the Small Business Perspective - Schaper, Michael T.; Lee, Cassey (Book collections on Project MUSE., 2016)
Small and medium-sized enterprises (SMEs) account for more than 90 per cent of all businesses in the Asia-Pacific region - an area which is rapidly updating its competition laws and regulations to encourage greater entrepreneurship and open, dynamic economies. Yet SMEs are almost invisible when those competition policies and laws are developed and enforced. SMEs are often quite different businesses than large, multinational corporation, but their nature, significance and characteristics are often overlooked. This book seeks to rectify the relative neglect in research and policy discussions on the role of the SME sector in competition policy and law. Drawing on contributions from a wide range of competition regulators, lawyers, academics, consultants and advisers to the SME sector, it addresses such important issues as: perceptions and views of small businesses about competition law; regulator engagement and education of the SME sector; the link between competition law and economic growth; franchising, SMEs and competition law; issues in enforcing competition law against SMEs; the role of Chinese family firms; trade, professional and industry associations; country case studies from Vietnam, Singapore, Indonesia, Malaysia, China, South Korea, Hong Kong SAR, Japan and the Pacific Islands.